THE FORMATION PROCESSES OF COOPERATION IN THE EDUCATION SECTOR BETWEEN UZBEKISTAN AND SOUTH KOREA - M. T. Alohanov (Journal Park Publishing, 2024)
This article highlights the stages of development of the international cooperation of the Republic of Uzbekistan with South Korea in the education sector, the country where cooperation is established, the results of cooperation, and plans. Furthermore, it analyses the reforms carried out in the field of education during the independence in Uzbekistan.
Keywords: Education, reform, civilization, subject, country, culture, scientist, academy, coexistence, law, government, benefit.